ЭТНОЛИНГВИСТИКА – ЭТНОСТЫ ТИЛ АРҚАЛЫ ТАНЫЎ - Зайрова, Қ. (SCIENCE and SOCIETY, 2023)
This article deals with the study of language problems from an ethnolinguistic perspective in close connection with the culture, customs, traditions and beliefs of the people. From an ethnolinguistic point of view, it has been proved that phraseological units, proverbs and sayings contain people's ideas about the world.
Keywords: ethnolinguistics; ethnos; nation; anthropocentric paradigm; human understanding; proverbs and sayings; phraseological words